KAJIAN YURIDIS TERHADAP IMPLEMENTASI OTONOMI KHUSUS DI PROVINSI PAPUA - Ma'adul Yaqien Makkarateng (Institut Agama Islam Negeri Bone, 2020)
This study discusses the concept of the Indonesian state as stated in Article 18 of the 1945 Constitution of the Republic of Indonesia concerning the implementation of regional autonomy. the interests of the local community. One area that has the potential to implement special autonomy in Indonesia is Papua Province for the sake of accelerating the realization of justice and social welfare. Social welfare can be achieved by means of rehabilitation (recovery and capacity building), social security (guaranteeing the fulfillment of basic needs), empowerment (empowering the community to meet their needs independently with existing resources and potential), social protection (prevention of social vulnerability so that their needs can be fulfilled). basic requirements are met), and social assistance to maintain a normal life.